2022
DOI: 10.1039/d1cp05501a
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and dielectric properties of solution combustion synthesized LaFeO3, LaFe0.9Mn0.1O3, and LaMnO3 perovskites

Abstract: Nanocrystalline LaFeO3, LaFe0.9Mn0.1O3, and LaMnO3 perovskites have been synthesized by a novel solution combustion route, wherein oxalyl dihydrazide has been used as a fuel. These materials have been characterized by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 68 publications
1
0
0
Order By: Relevance
“…The FTIR spectra captured by the Bruker spectrometer were used to validate the creation of the metal-oxide phase, and the occurrence of Mn-O stretching vibrations. The observed band at 560 cm -1 is due to the stretching vibration of Mn-O bonds, which agrees with a study conducted in 2020 [29].Also, it is observed that there are several distinct peaks at 654 and 429cm -1 which attributed to Mn-O vibrations [30].Moreover, the absence of any peak in the region (4000-3000) cm -1 indicates that the nanoparticles are free of any trace of water molecules, which may be due to solvent residues or air moisture [31]. This arrangement in the crystal size is in agreement with the arrangement that was calculated from the Debye-Scherrer equation.…”
Section: Methodssupporting
confidence: 91%
“…The FTIR spectra captured by the Bruker spectrometer were used to validate the creation of the metal-oxide phase, and the occurrence of Mn-O stretching vibrations. The observed band at 560 cm -1 is due to the stretching vibration of Mn-O bonds, which agrees with a study conducted in 2020 [29].Also, it is observed that there are several distinct peaks at 654 and 429cm -1 which attributed to Mn-O vibrations [30].Moreover, the absence of any peak in the region (4000-3000) cm -1 indicates that the nanoparticles are free of any trace of water molecules, which may be due to solvent residues or air moisture [31]. This arrangement in the crystal size is in agreement with the arrangement that was calculated from the Debye-Scherrer equation.…”
Section: Methodssupporting
confidence: 91%
“…Figure 3 shows the FTIR spectrum obtained from the powders, where two absorption bands positioned at 437 cm −1 and 603 cm −1 are clearly observed. The weak absorption band located at 437 cm −1 is attributed to the bending vibrations of the Fe-O bonds within the FeO 6 octahedron [32], while the intense absorption band positioned at 603 cm −1 is a result of the stretching vibration of the Cr-O bonds within the CrO 6 octahedra [33]. Thus, the octahedral coordination of Fe and Cr ions with oxygen ions (O 2− ) in the powders is confirmed by the FTIR spectrum.…”
Section: Microstructural Characterizationmentioning
confidence: 67%
“…The XRD pattern matches the rhombohedral crystalline form of the LaMnO3 perovskite with the R-3c group corresponding to JCPDS No. 50-0298 satisfactorily [57]. The diffraction peaks of CLMO were prominently detected at 2θ angles of 22.9°, 32.5°, 40.1°, 46.5°, 52.5°, 58.1°, 68.2°, 69.3°, and 77.9°, which are archived for (012), ( 110), ( 202), ( 024), ( 122), ( 214), ( 220), (208), and (128) facets of the lattice, respectively.…”
Section: Characterization Techniquesmentioning
confidence: 94%